Housing As We Grow Older: Taking Stock - Virginia Peart; Carolyn Wilken (EDIS)
This document is Fact Sheet FCS 3187, a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: November 2002. First published: January 1994. Revised: November 2002. Originally published as SAH-1 and adapted for use in Florida from "Planning Ahead for Elder Care: Decisions About Housing" and "Long-Term Care: Services for the Individual."